2017
DOI: 10.1080/15532739.2017.1293581
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of physical activity and sport participation among young transgender adults who are medically transitioning

Abstract: Background: Transgender people (those who feel incongruence between the gender they were assigned at birth and their gender identity) engage in lower levels of physical activity compared to cisgender people (non-transgender). Several factors have been shown to affect physical activity engagement in the cisgender population however; the physical activity experiences of young transgender adults have not been explored. It was therefore the aim of the current study to understand what factors are associated with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 30 publications
2
71
1
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w given that 79% of survey respondents felt that transphobia was a barrier to participating in 397 sport. 56 This lack of association in our study may be explained by the fact that some 398 transgender people anticipate, as opposed to experience, transphobia 20,57 and the measure in 399 the current study only asked about the experience of transphobia. In addition, the percentage 400 of physical activity explained by the regression models was low.…”
Section: Males (Ie By Increasing Their Levels Of Body Satisfactioncontrasting
confidence: 44%
See 2 more Smart Citations
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w given that 79% of survey respondents felt that transphobia was a barrier to participating in 397 sport. 56 This lack of association in our study may be explained by the fact that some 398 transgender people anticipate, as opposed to experience, transphobia 20,57 and the measure in 399 the current study only asked about the experience of transphobia. In addition, the percentage 400 of physical activity explained by the regression models was low.…”
Section: Males (Ie By Increasing Their Levels Of Body Satisfactioncontrasting
confidence: 44%
“…Based on the amount of barriers that transgender people experience when engaging in 347 physical activity and sport 20,21 it is understandable that greater self-esteem was found to be 348 This study found that once cross-sex hormone treatment had commenced, self-esteem was no 361 longer the best statistical predictor of physical activity. In addition, transgender people who 362 were taking cross-sex hormones engaged in significantly more physical activity than 363 participants who were not.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Many transgender people, particularly prior to their physical transition, face considerable challenges. These challenges can be physiological (development of some of the secondary sexual characteristics of the sex assigned at birth), social (lack of social support, rejection, discrimination, victimisation, transphobia) [ 3 12 ] and psychological (e.g. anxiety, depression, low self-esteem) [ 3 , 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by a review of existing body dissatisfaction measures that are currently used to assess patient outcomes at transgender health services (Jones et al, 2016). Next, in-depth interviews with 14 transgender people attending a national transgender health service in the UK were undertaken as part of a larger study (Jones, Arcelus, Bouman, & Haycraft, 2017). These interviews highlighted how distress and dissatisfaction with gender, associated mental wellbeing, and life satisfaction improved over the treatment process.…”
Section: Development Of the Gender Congruence And Life Satisfaction Smentioning
confidence: 99%